PENGARUH PENERAPAN SELF ASSESSMENT SYSTEM, PENGETAHUAN WAJIB PAJAK, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi pada Wajib Pajak Orang Pribadi Non Karyawan di KPP Pratama Ciamis Tahun 2017) - Irna Liani Putri Anjanni; Dini Wahjoe Hapsari; Ardan Gani Asalam (Jurnal Akademi Akuntansi, 2019)
The purpose of this research is to find out how the effect implementation of Self Assessment System (SAS), Tax Payer Knowledge (PWP), Service Quality (KP) on Non-employee Personal Taxpayer Compliance at Tax Service Pratama Ciamis (KPP) in 2017. This study uses incidental sampling with a total sample of 99 non-employee Personal Taxpayers at KPP Pratama Ciamis. The analytical method in this study is descriptive statistical analysis, multiple linear regression analysis, and hypothesis analysis. This study shows that the implementation of SAS, PWP, and KP simultaneous affects the compliance of non-employee individual taxpayers at KPP Pratama Ciamis, and then the results of partial testing show that they are have a positive and significant effect on the compliance of non-employee Personal Taxpayers at KPP Pratama Ciamis.Keywords: Non-employee Personal Taxpayers, Self Assessment System, Service Quality, Taxpayer Knowledge, Taxpayer Compliance